The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1029-242x-2012-269
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds for the number of spanning trees of graphs

Abstract: In this paper, we present some upper bounds for the number of spanning trees of graphs in terms of the number of vertices, the number of edges and the vertex degrees. MSC: 05C05; 05C50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It may be remarked that Corollary 5.3 can be proved using Proposition 5.5 and induction as well. The following bound has been obtained in [6].…”
Section: Maximizing the Number Of Spanning Trees In A Bipartite Graphmentioning
confidence: 99%
“…It may be remarked that Corollary 5.3 can be proved using Proposition 5.5 and induction as well. The following bound has been obtained in [6].…”
Section: Maximizing the Number Of Spanning Trees In A Bipartite Graphmentioning
confidence: 99%
“…The key idea behind the bound above is to apply the AM-GM inequality to the normalized eigenvalues. Other recent advances in constructing upper bounds for the number of spanning trees can be found in [9], another overview is given in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Though, for a bipartite graph we know some improvement of the bound (1) . For example, in [8] the following upper bound was shown for a bipartite connected graph…”
Section: Introductionmentioning
confidence: 99%
“…Now, we give some known upper bounds on t ( G ): Grimmett [ 11 ]: Grone and Merris [ 12 ]: Nosal [ 13 ]: for r -regular graphs, Cvetković et al (see [ 5 , page 222]): where is the number of edges of , Das [ 14 ]: Zhang [ 15 ]: where a = (( n ( n −1) − 2 m )/2 mn ( n −2)) 1/2 , Feng et al [ 16 ]: Li et al [ 17 ]: Bozkurt [ 18 ]: where b = (( n −1−Δ 1 )/ n ( n −2)Δ 1 ) 1/2 , Das et al [ 19 ]: …”
Section: Introductionmentioning
confidence: 99%
“…However, Das et al [ 19 ] proved that ( 11 ) is not true for K n . In [ 15 , 16 , 18 ] the authors showed that ( 8 ) is better than ( 3 ), ( 9 ) is better than ( 7 ) and ( 10 ), and ( 12 ) is better than ( 4 ). For more bounds and the relations between the number of spanning trees and the structural parameters of graphs such as connectivity, chromatic number, independence number, and clique number, see [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%